FIGURE 14 in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 14. Pergamaster incertus (USNM 1081793) A. Abactinal surface. B. (inset) Close up of abactinal plates and madreporite. C. Abactinal view of arm showing superomarginals not abutted. D. Actinal surface and furrow spines. E. Lateral view of marginal plate series. USNM E13415 (ex. P. synaptorus) F. Abactinal arm showing abutted superomarginals over midline. Scale Bar= 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 36, DOI: 10.5281/zenodo.276783